Post-therapeutic cure criterion in chronic Chagas disease using Trypanosoma cruzi chimeric proteins - Pavan, Tycha Bianca Sabaini (2024)
Chagas disease (CD) is a neglected disease caused by Trypanosoma cruzi Chagas, 1909. Causative treatment can be achieved with two drugs: benznidazole or Nifurtimox. There are some gaps that hinder progress in eradicating the disease. There is no test that can efficiently assess cure control after treatment. Currently, the decline in anti-T. cruzi antibody titres is assessed with conventional serological tests, which can take years. However, the search for new markers of cure must continue to fill this gap. The present study aimed to evaluate the decline in serological titres using chimeric proteins after treatment with benznidazole in chronic patients diagnosed with CD. It was a prospective cross-sectional cohort study between 2000 and 2004 of T. cruzi-positive participants from the Añatuya region (Argentina) treated with benznidazole. Serum samples from ten patients were collected before treatment (day zero) and after the end of treatment (2, 3, 6, 12, 24 and 36 months). For the detection of anti-T. cruzi antibodies, an indirect ELISA was performed using two chimeric recombinant proteins (IBMP-8.1 and IBMP-8.4) as antigens. The changes in reactivity index within the groups before and after treatment were evaluated using the Friedman test. All participants experienced a decrease in serological titres after treatment with benznidazole, especially IBMP-8.1. However, due to the small number of samples and the short follow-up period, it is premature to conclude that this molecule serves as a criterion for sustained cure. Further studies are needed to validate tests based on these or other biomarkers to demonstrate parasitological cure.